Examination of pretreatment methods for DNA extraction from nails. (December 2022) - Ochiai, Eriko; Asogawa, Minoru; Irie, Wataru; Sasaki, Chizuko; Nakamaru, Naomi; Sakamoto, Momoko; Nagato, Junpei; Saito, Junichiro; Sugisawa, Masatoshi; Satoh, Fumiko
Abstract: In the conventional method of DNA extraction from nails, it takes approximately half a day to dissolve the nails. In this study, we examined whether using the HOrizontal Nail MAshing (HONMA) method, in which pressure is applied to the nail to crush it flat and increase its surface area, would improve DNA extraction efficiency. Fingernails (5 mg) provided by ten volunteers were used as samples. Nail pieces (1–3 pieces), shredded with nail clippers, were thinly stretched by applying 2 t of pressure to each piece using a hydraulic press. DNA was extracted by incubation at 56 °C for 10 min and 1 h during proteolysis. DNA yield from the nails pretreated using the HONMA method increased by 0.20–7.10 times compared with that from unprocessed nails. In particular, 10-min incubation using the HONMA method resulted in an average 2.05-fold increase in DNA yield compared with that under overnight incubation. However, the impact of using the HONMA method varied widely among individuals, and the amount of extracted DNA decreased in some cases, suggesting that the yield may differ depending on the nail quality.